Rozwój proekologicznej produkcji drobiarskiej jako czynnik rozwoju obszarów wiejskich - Krawczyk, Józefa; Sokołowicz, Zofia (Development of Ecological Poultry Production as a Factor in the Development of Rural Areas, 2006)
The development of intensive production methods has led to the establishment of very large farms and the elimination of small producers from the market. The industrialization and the intensification of production are a source of much controversy among consumers, hence the growing recent interest in the development of extensive poultry breeding systems, including ecological farms. Due to the planned increase in EU structural funds to support ecological farms, improve animal welfare and conserve native breeds, it is expected that the intensive industrial methods of poultry breeding will be stopped. If producers use the Rural Development Plan funds reasonably to support competitiveness in agriculture, it will also be possible to improve the marketing of poultry products obtained in ecological systems of production and to promote many quality products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 710-715